Studies on the reproductive dynamics of Pleoticus muelleri (Bate, 1888) (Crustacea, Decapoda, Solenoceridae) of Patagonia, Argentina Estudios sobre la dinámica reproductiva del langostino Pleoticus muelleri (Bate, 1888) (Crustacea, Decapoda, Solenoceridae) de Patagonia, Argentina - Mónica Fernández; María I Iorio; Daniel Hernández; Gustavo Macchi (Latin American Journal of Aquatic Research, 2012)
Certain aspects of the reproductive dynamics of Argentine red shrimp Pleoticus muelleri (Bate, 1888), distributed between 42°-47°S and 62°W, were investigated. Data and samples were collected during 36 INIDEP research cruises and 87 commercial fishing fleet trips between 1994-2010. Mature and inseminated females size structure as well as the frequency distribution of macroscopic maturity stages of adult females were analyzed on space-time bases. The seasonal development of ovarian maturity stages microscopically determinated was also assessed. Statistical treatment of data included multivariate scaling and cluster analysis. The reproductive activity of the shrimps showed latitudinal differences concerning its onset and duration that could be associated with the variability of environmental conditions. We discuss a shoreward movement of spawning females related to the presence of coastal hydrographic processes that would ensure retention and food for survival of early life stages. Se estudian ciertos aspectos de la dinámica reproductiva del langostino Pleoticus muelleri (Bate, 1988) en el área comprendida entre 42°-47°S y 62°W. Los datos y las muestras analizadas provienen de 36 campanas de investigación del INIDEP y de 87 viajes de la flota comercial langostinera realizados entre 1994 y 2010. Se analiza la estructura de tallas de las hembras maduras e impregnadas, al igual que la distribución de frecuencias de los distintos estadios de madurez sexual de las hembras adultas diferenciados macros-cópicamente, desde un enfoque espacio-temporal. La evolución estacional de los estadios de desarrollo ovárico determinados histológicamente también fue contemplada. El tratamiento estadístico de los datos comprendió un escalamiento multivariado y un análisis de agrupamiento jerárquico. La actividad reproductiva del langostino presenta diferenciaciones latitudinales con respecto a su inicio y duración que podría relacionarse con la variabilidad de las condiciones ambientales. Se discute la relación entre el movimiento hacia la costa de las hembras impregnadas y la presencia de procesos hidrográficos costeros que asegurarían la retención y disponibilidad de alimento para la supervivencia de las primeras etapas de vida.